DETERMINAN KEJADIAN ANEMIA PADA REMAJA PUTRI USIA 15-24 TAHUN PADA DAERAH PEDESAAN DI INDONESIA (ANALISIS DATA RISKESDAS 2018) - Adhi, Kadek Tresna; Asmin, Maria Lusi Putri (ARCHIVE OF COMMUNITY HEALTH, 2024)
Anemia in the age group of 15-24 years in Indonesia is a nutritional problem that is of great concern. The purpose of this study was to find out what factors are associated with the incidence of anemia in young women aged 15-24 years in rural areas in Indonesia. This study used secondary data obtained from the 2018 Riskesdas data. The research design used was a cross-sectional study with a sample of 1158 young women aged 15-24 years. Data analysis was performed using descriptive analysis, chy-square and multiple logistic regression tests. The results of the analysis show that the determinants that affect the incidence of anemia in young women aged 15-24 years in rural areas of Indonesia are the amount of vegetable consumption (p<0.001, aOR= 15.03, 95% CI= 8.05-28.03), the age of the adolescent daughter (ip<0.001, aOR=i2.81, 95%CI=i1.61-4.91) and mother's occupation i(p=0.016, aOR=i1.95, i95%CI=1.33-3.35 ), each variable contributes to an increased risk of anemia in female adolescents. Therefore, it is necessary to intensify health promotion and education related to the prevention of anemia in young women, especially in rural areas of Indonesia, especially the importance of consuming blood-boosting tablets (TTD) to prevent the risk of anemia in young women aged 15-24 years in rural areas of Indonesia. Keywords: Anemia, Indonesian young women, Rural